Getting Fit

Algebra Level 3

As part of his daily exercise, Calvin takes a walk a fixed course. He generally does so at the same speed. On a day that he's feeling energetic, he walks 2 2 km/hr faster than normal, and found that it took half the usual time plus 15 15 minutes to finish the course. On a day that he's feeling lethargic, he walks 1 1 km/hr slower than normal, and found that it takes 30 30 minutes more than the normal time. What is the distance (in km) of the course that he walks everyday?

Image source: Wikipedia


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

18 solutions

let x be the distance of of the course that calvin walks every day, and let the t be the time. the equation will be x = v t x=vt when he is feeling energetic, his speed will be v+2 and the time will be (t/2)+(1/4), thus we get x = ( v + 2 ) ( t 2 + 1 4 ) x=(v+2)(\frac{t}{2}+\frac{1}{4}) when he is feeling lethargic, his speed will be v-1 and the time will be t+(1/2), thus we get x = ( v 1 ) ( t + 1 2 ) x=(v-1)(t+\frac{1}{2}) subtitute the first equation for x value ( v + 2 ) ( t 2 + 1 4 ) = ( v 1 ) ( t + 1 2 ) (v+2)(\frac{t}{2}+\frac{1}{4})=(v-1)(t+\frac{1}{2}) v + 2 v 1 = 2 \frac{v+2}{v-1}=2 4 = v 4=v now we can find value of t x = v t x=vt x = 4 t x=4t 4 t = ( 4 1 ) ( t + 1 2 ) 4t=(4-1)(t+\frac{1}{2}) 4 t = 3 t + 3 2 4t=3t+\frac{3}{2} t = 3 2 t=\frac{3}{2}


x = v t x=vt x = 4 × 1.5 x=4\times 1.5 x = 6 x=\boxed{6}

Instead of 't' you could have written s/v. So the solution could have been in a bit shorter...

Amlan Mishra - 7 years, 5 months ago

nice solution

ashis das - 7 years, 5 months ago

cool... why didnt i think of this?

Benjamin Fonua - 7 years, 4 months ago

You have done it well.

A Former Brilliant Member - 7 years, 4 months ago

Nicely solved

YASH KASAT - 7 years, 3 months ago

i don't understand. :3 but your solution is nicely done :))

Jarryl Royd Almocera - 7 years, 3 months ago

you're just 16 years old and could solve such mathematical problem...minds if i wan interview u? :3

Hazim Afifi - 7 years, 2 months ago

superb

Shakil Ahmad - 7 years, 5 months ago

great!!!

PUSHPESH KUMAR - 7 years, 4 months ago
敬全 钟
Dec 31, 2013

We let s s to be the speed, and t t to be the time in minutes. Therefore, we can simplify the problem a little bit by writing the equation below,

( s + 2 ) ( t 2 + 15 ) = ( s 1 ) ( t + 30 ) (s+2)(\frac{t}{2}+15)=(s-1)(t+30)

s t 2 + 15 s + t + 30 = s t + 30 s t 30 \frac{st}{2}+15s+t+30=st+30s-t-30

2 t + 60 = s t 2 + 1 2t+60=\frac{st}{2}+1

4 t + 120 = s t + 30 s 4t+120=st+30s

4 ( t + 30 ) = s ( t + 30 ) 4(t+30)=s(t+30)

s = 4 s=4

Now, we have to substitute s = 4 s=4 to both sides and equate one of the sides with d s = t d 4 = t d = 4 t \frac{d}{s}=t\implies \frac{d}{4}=t\implies d=4t , such that d d is the distance. If we equate the equation above again, it will bring us to nowhere.

3 ( t + 30 ) = 4 t 3(t+30)= 4t

t = 30 \implies t=30

Then, we have to convert t t into hours, which means that t = 1 2 h r s t=\frac{1}{2} hrs . Substitute both values into d = 4 t d=4t , we get d = 6 d=\boxed6 , which is our desired answer.

t = 90. d = 4 * 1.5 = 6

Tong Choo - 7 years, 5 months ago

In the last step, you made a mistake. 3 ( t + 30 ) = 4 t 3 t + 90 = 4 t t = 90 3(t+30)=4t \implies 3t+90=4t \implies t=90 min i.e t=1.5 hrs.

t=90 and not 30

Prasun Biswas - 7 years, 5 months ago

Log in to reply

Aww. I forget to type the 1. Sorry, my typo mistake

敬全 钟 - 7 years, 5 months ago

What happened to the 15s in the third step?

Rahul Sharma - 7 years, 5 months ago
Jan J.
Dec 31, 2013

Suppose that normally he walks distance d d at speed v v and in time t t , then we are given system { v + 2 = d t 2 + 0.25 v 1 = d t + 0.5 v = d t \begin{cases} v + 2 = \frac{d}{\frac{t}{2} + 0.25} \\ v - 1 = \frac{d}{t + 0.5} \\ v = \frac{d}{t} \end{cases} Which is very easy to solve to get ( v , d , t ) = ( 4 , 6 , 1.5 ) (v,d,t) = (4,6,1.5) , so the answer is 6 \boxed{6}

solved by higher maths.......I guess.

ashwani singh - 7 years, 4 months ago

superb

sudhir kumar - 7 years, 4 months ago
Piyushkumar Palan
Dec 31, 2013

Let Calvin's normal speed be x x km/hr and usual time be t t hr. Distance be d d km.

d = x t = ( x + 2 ) ( t 2 + 1 4 ) = ( x 1 ) ( t + 1 2 ) d = xt = (x + 2)(\frac{t}{2}+\frac{1}{4}) = (x-1)(t+\frac{1}{2})

x t = ( x 1 ) ( t + 1 2 ) x = 2 t + 1 xt = (x-1)(t+\frac{1}{2}) \implies x = 2t + 1

Putting x = 2 t + 1 x = 2t + 1 in x t = ( x + 2 ) ( t 2 + 1 4 ) xt = (x + 2)(\frac{t}{2}+\frac{1}{4})

we get ( 2 t + 1 ) t = ( 2 t + 3 ) ( 2 t + 1 4 ) 4 t 2 4 t 3 = 0 t = 3 2 o r 1 2 (2t + 1)t = (2t + 3)(\frac{2t + 1}{4} ) \implies 4t^2 - 4t - 3 = 0 \implies t = \frac{3}{2} or \frac{-1}{2}

Finally,

t = 3 2 t = \frac{3}{2} hr,

x = 2 3 2 + 1 = 4 x= 2\cdot \frac{3}{2}+1=4 km/hr,

d = x d = 6 d = x\cdot d = \boxed6 km.

Abubakarr Yillah
Jan 10, 2014

Let the of the course distance be d {d}

the normal speed be s {s}

and the normal time be t {t}

we know that d = s × t . . . . . ( 1 ) {d}={s}\times{t}.....(1)

In the first instance d = ( s + 2 ) × ( t 2 + 1 4 ) . . . . . ( 2 ) {d}=(s+2)\times(\frac{t}{2}+\frac{1}{4}).....(2)

In the second instance d = ( s 1 ) × ( t + t 2 ) . . . . . ( 3 ) {d}=(s-1)\times(t+\frac{t}{2}).....(3)

Note that the times given in minutes are converter into hours hence 1/4hr and 1/2hr

i.e. ( s 1 ) ( t + t 2 ) = ( s + 2 ) ( t 2 + 1 4 ) = s t (s-1)(t+\frac{t}{2})=(s+2)(\frac{t}{2}+\frac{1}{4})={st}

Solving, ( s + 2 ) ( t 2 + 1 4 ) = s t (s+2)(\frac{t}{2}+\frac{1}{4})={st}

i.e. s t 2 + s 4 + t + 12 = s t \frac{st}{2}+\frac{s}{4}+{t}+{1}{2}={st}

which simplifies to 2 s t 4 t s = 2..... ( 4 ) {2st}-{4t}-{s}={2}.....(4)

solving, ( s 1 ) ( t + t 2 ) = s t (s-1)(t+\frac{t}{2})={st}

i.e. s t + s 2 t 1 2 = s t {st}+\frac{s}{2}-{t}-\frac{1}{2}={st}

which simplifies to s 2 t = 1 {s-2t}={1}

from which s = 1 + 2 t . . . . . ( 5 ) {s}={1+2t}.....(5)

substituting.....(5) into.....(4) we get

2 t + 4 t 2 4 t 1 2 t = 2 2t+4{t}^2-4t-1-2t=2

which simplifies to 4 t 2 4 t 3 = 0 {4t^2}-{4t}-{3}={0}

and ( 2 t 3 ) ( 2 t + 1 ) = 0 (2t-3)(2t+1)={0}

so ( 2 t 3 ) = 0 (2t-3)={0}

and t = 3 2 h r s {t}=\frac{3}{2}hrs as the only positive value of t

But s = 1 + 2 t {s}={1+2t}

i.e. s = 1 + 2 ( 3 2 ) {s}={1+2(\frac{3}{2})}

and s = 4 k m / h r {s}={4km/hr}

from.....(1) d = s × t {d}={s}\times{t}

i.e. d = 4 × 3 2 {d}={4}\times{\frac{3}{2}}

Hence distance of the course equals 6 k m \boxed{6km}

does it have to be this long?

Anirudh Vasudevan - 7 years, 4 months ago
Nagabhushan S N
Jan 8, 2014

Distance=velocity Time In All Cases, distance travelled is same 2xy=(x+2)(y+0.25)=(x-1)(2y+0.5) 2xy=xy+0.25x+2y+0.5=2xy+0.5x-2y-0.5 xy-0.25x-2y-0.5=0 0.5x-2y-30=0 Subtracting xy-0.75x=0 x(y-0.75)=0 x!=0 implies y=0.75hrs 0.5x-2y-0.5=0 0.5x-1.5-0.5=0 x=4 Distance=2xy=2 4*0.75=6kms

Noel Lo
Jan 8, 2014

Let x be the distance in kilometres and v km/h be the usual speed. We can construct two equations x/(v+2) = (1/2)(x/v) = 1/4 and x/(v-1) = x/v +1/2. Doubling the first equation we get 2x/(v+2) = x/v + 1/2. Just nice the right side of the two equations are exactly the same!!! Hence 2x/(v+2) = x/(v-1). Eliminating x we get 2(v-1) = v+2 which gives us v=4. Simple substitution and equation solving tells us that x=6.

in x/(v+2) = (1/2)(x/v) = 1/4 you made a type mistake, the correct equation is x/(v+2) = (1/2)(x/v) + 1/4

Sándori Klára - 7 years, 5 months ago
Mamatha Balagopal
Jan 21, 2014

let s=distance in km, v=normal speed and t=normal time taken to complete the course. hence, we can write (v+2) (t/2+1/4) = (v-1) (t+1/2) = v*t (here, 15min=1/4hrs and 30min=1/2hrs)

solving these equations we get,

v=4 km/hr and t=3/2=1.5 hrs

so, s=v t=4 1.5= 6 km

Distance(d) = speed(s) * Time(t) d=st= (s+2)(t/2 + ¼) ……..(i)and d=st = (s-1)(t + ½)………..(ii) or, (s+2)(t/2 + ¼) = (s-1)(t + ½) or,(s+2)(2t+1)/4 = (s-1)(2t+1)/2
or, (s+2)(2t+1) = 2(s-1)(2t+1) or, 2st+s+4t+2 = 4st+2s-4t-2 or, 2st-8t+s-4=0 or, 2t(s-4)+1(s-4)=0 or,(s-4)(2t-1)=0 s=4,t=-1/2 putting s=4 in equation(ii),we get t= 3/2 then Distance = 4*(3/2)=6

Shibin Kuriakose
Jan 19, 2014

let distance be d and the speed be s

time will be d\s

* d/(s+2) = t/2 + 1/4 *

ie (d/(s+2) - 1/4 ) X 2 = t

2d/(s+2) - 1/2 = t ---- 1

d/(s-1) = t + 1/2

ie d/(s-1) - 1/2 = t ---- 2

1 and 2 =====> s=4 , d=6

Shahriar Ahmed
Jan 18, 2014

s=vt s=(v+2)(t/2+1/4) s=(v-1)(t+1/2)=vt+v/2-t-1/2 v/2-t-1/2=0 or -2t=1-v...(1) s=2t+v/2+1.....(2) s=vt..........(3) vt-2t-v/2-1=0 or vt+1-v-v/2-1=0 or t=3/2 from 1 v=4 s=3/2*4=6

Ahsanul Habib
Jan 6, 2014

suppose,distance of the course is x km

speed=y

time=x/y

the equations are,

(x)/(y+2)=(x)/(2y)+(1)/(4)..........(1)

(x)/(y-1)=x/y+1/2.......(2)

Dividing equation (1) By equation (2) & using componendo-divodendo method we get the value of y=4

putting the value of y=4 in the equation (1) we get the distance, x=6 km (Ans)

Let x be the rate. Let t be the time (in hours) so 15 mins = ( 1 4 \frac{1}{4} ) and 30 minutes is ( 1 2 \frac{1}{2} ).

  • 1st condition : (x + 2)( t 2 + 1 4 \frac{t}{2} + \frac{1}{4} ) = d
  • 2nd condition : (x - 1)(t + 1 2 \frac{1}{2} ) = d

    - 3rd condition: xt = d

Equating 1st and 2nd condition for the same d:

  • ( 2 t + 1 ) ( x + 2 ) 4 \frac{(2t + 1)(x + 2)}{4} = ( 2 t + 1 ) ( x 1 ) 2 \frac{(2t + 1)(x - 1)}{2}
  • Cancel "(2t + 1)"

    - x = 4

Substituting "4" into the values of 1st / 2nd condition and equating with the 3rd.

  • ( 2 t + 1 ) ( 4 1 ) 2 \frac{(2t + 1)(4 - 1)}{2} = 4t

    - t = 3 2 \frac{3}{2}

Thus

  • d = xt
  • d = ( 3 2 \frac{3}{2} )(4)
  • d = 6 \boxed{6}
Prasun Biswas
Jan 4, 2014

Let us take the speed as x x km/hr and time as t t min. We know the formula, Distance = = Speed × \times TIme. From that and according to the problem , we have two equations of the distance travelled(d) as---

d = ( x + 2 ) ( 1 2 t + 15 ) d=(x+2)(\frac{1}{2}t+15) ...(i) and d = ( x 1 ) ( t + 30 ) d=(x-1)(t+30) ....(ii)

From (i) and (ii), we have,

( x + 2 ) ( 1 2 t + 15 ) = ( x 1 ) ( t + 30 ) (x+2)(\frac{1}{2}t+15)=(x-1)(t+30)

( x + 2 ) ( t + 30 ) 2 = ( x 1 ) ( t + 30 ) \implies \frac{(x+2)(t+30)}{2}=(x-1)(t+30)

x + 2 = 2 ( x 1 ) x + 2 = 2 x 2 x = 4 \implies x+2=2(x-1) \implies x+2=2x-2 \implies x=\boxed{4}

We also have the standard equation as d = x × t d=x\times t ....(iii)

From (ii) and (iii), we have,

( x 1 ) ( t + 30 ) = x t ( 4 1 ) ( t + 30 ) = 4 t 3 ( t + 30 ) = 4 t 3 t + 90 = 4 t t = 90 (x-1)(t+30)=xt \implies (4-1)(t+30)=4t \implies 3(t+30)=4t \implies 3t+90=4t \implies t=\boxed{90}

So, Speed = 4 =4 km/hr and Time = 90 =90 min = 90 60 =\frac{90}{60} hr = 3 2 =\frac{3}{2} hr.

Distance = = Speed × \times Time = ( 4 × 3 2 ) =(4\times \frac{3}{2}) km = ( 2 × 3 ) =(2\times 3) km = 6 =\boxed{6} km

Arpit Sah
Jan 1, 2014

Let the normal speed of Calvin be x km/hr.

Let the time taken by Calvin to walk a fixed course be y hr.

Therefore, distance of the course = xy km

According to first condition:

New speed = (x+2) km/hr

New time taken = ( y 2 \frac{y}{2} + 15 60 \frac{15}{60} ) hr

(x+2) ( y 2 \frac{y}{2} + 15 60 \frac{15}{60} ) = xy

(x+2) ( y 2 \frac{y}{2} + 1 4 \frac{1}{4} ) = xy

(x+2) ( 2 y 4 \frac{2y}{4} + 1 4 \frac{1}{4} ) = xy

(x+2) ( 2 y + 1 4 \frac{2y+1}{4} ) = xy

( x + 2 ) ( 2 y + 1 ) 4 \frac{(x+2)(2y+1)}{4} = xy

(x+2)(2y+1) = 4xy

2xy + 4y + x + 2 = 4xy

x + 4y + 2 = 2xy ..................(i)

According to second condition:

(x-1)(y+ 1 2 \frac{1}{2} ) = xy

(x-1)(2y+1) = 2xy

2xy - 2y +x -1 = 2xy .................(ii)

2xy - 2y +x -1 = x + 4y +2 [From (i)]

2xy = 6y + 3

x = 6 y + 3 2 y \frac{6y+3}{2y} .......................(iii)

2xy - 2y +x -1 = 2xy [From (ii)]

x - 2y -1 = 0

6 y + 3 2 y \frac{6y+3}{2y} - 2y - 1 = 0

6 y + 3 4 y 2 2 y 2 y \frac{6y+3-4y^{2} - 2y}{2y} = 0

4y+3- ( 4 y ) 2 (4y)^{2} = 0

( 4 y ) 2 (4y)^{2} - 4y - 3 = 0

( 4 y ) 2 (4y)^{2} - 6y + 2y - 3 = 0

2y(2y-3) + 1(2y-3) = 0

(2y-3)(2y+1) = 0

2y - 3 = 0

y = 3 2 \frac{3}{2} hr

Therefore, x = 4 km/hr

xy = 6 km

Hence the distance of the course that Calvin walks every day is 6km.

Ayon Pal
Dec 31, 2013

Let, usual time he takes to finish the course x x hrs with normal speed y y km/hrs.

So, the total distance of the course is x y xy km

So, when he walks faster it takes ( x 2 + 15 60 ) ( x 2 + 1 4 ) ( \frac{x}{2} + \frac{15}{60}) \implies ( \frac{x}{2} + \frac{1}{4}) hrs with speed ( y + 2 ) (y+2) km/hrs and when he walks slower it takes ( x + 30 60 ) ( x + 1 2 ) (x + \frac{30}{60}) \implies (x + \frac{1}{2} ) hrs with speed ( y 1 ) (y-1) km/hrs.

In both case the total distance is same ( x y ) (xy) .

We know s p e e d × t i m e = d i s t a n c e speed \times time = distance

So, we get two equation ( x 2 + 1 4 ) × ( y + 2 ) = x y . . . . . . . . ( i ) \implies ( \frac{x}{2} + \frac{1}{4}) \times (y+2) = xy ........(i)

And,

( x + 1 2 ) × ( y 1 ) = x y . . . . . . . . ( i i ) \implies (x + \frac{1}{2}) \times (y-1) = xy ........(ii)

Solving equations (i) and (ii), we get the normal time he takes x = 1.5 x = 1.5 hrs. and normal speed y = 4 y = 4 km/hrs.

So, the total distance of his course is x y 1.5 × 4 6 \implies xy \implies 1.5 \times 4 \implies \boxed{6} km.

Mukul Dhiman
Dec 31, 2013

Let s=normal speed, t=normal time and d=distance on solving the following equations for s and t: st = (s+2)(t/2+1/4) = (s-1)(t+1/2) we get, s=4 and t=3/2 hence, d=st=4*(3/2)=6

Rares B.
Dec 31, 2013

Let t t , d d , and v v be the time,distance and speed respectively . Using the formula s p e e d t i m e = d i s t a n c e speed*time=distance , we have the following system of equations : { v t = d ( v + 2 ) ( t 2 + 1 4 ) = d ( v 1 ) ( t + 1 2 ) = d { v t = d v t 2 + v 4 + t + 1 / 2 = d v t + v 2 t 1 / 2 = d { v t = d d 2 + v 4 + t + 1 / 2 = d d + v 2 t 1 / 2 = d \\\Rightarrow \begin{cases} vt=d \\ (v+2)(\frac{t}{2}+\frac{1}{4})=d \\ (v-1)(t+\frac{1}{2})=d \end{cases} \Rightarrow \begin{cases} vt=d \\ \frac{vt}{2}+\frac{v}{4}+t+1/2=d \\ vt+\frac{v}{2}-t-1/2=d \end{cases} \Rightarrow \begin{cases} vt=d \\ \frac{d}{2}+\frac{v}{4}+t+1/2=d \\ d+\frac{v}{2}-t-1/2=d \end{cases}

Adding the last two together: 3 d 2 + 3 v 4 = 2 d 3 v 4 = d 2 3 v 2 = d \frac{3d}{2}+\frac{3v}{4}=2d \Rightarrow \frac{3v}{4}=\frac{d}{2} \Rightarrow \frac{3v}{2}=d Substituting this in v t = d t = 3 2 vt=d \Rightarrow t=\frac{3}{2}

{ v t = d d 2 + v 4 + t + 1 / 2 = d d + v 2 t 1 / 2 = d { v t = d 2 d + v + 4 t + 2 = 4 d 2 d + v 2 t 1 = 2 d \begin{cases} vt=d \\ \frac{d}{2}+\frac{v}{4}+t+1/2=d \\ d+\frac{v}{2}-t-1/2=d \end{cases} \Rightarrow \begin{cases} vt=d \\ 2d+v+4t+2=4d \\ 2d+v-2t-1=2d \end{cases}

Substracting the last from the second : 6 t + 3 = 2 d 9 + 3 = 2 d d = 6 6t+3=2d \Rightarrow 9+3=2d \Rightarrow \boxed{d=6}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...